The Association of Body Size and Composition with Erectile Dysfunction in Older Men: Osteoporotic Fractures in Men (MrOS) Study - Garimella, Pranav S. (2013)
OBJECTIVES: To examine the association of body size and composition with erectile dysfunction (ED) in older men. DESIGN: Cross-sectional analysis of the Osteoporotic Fractures in Men study. SETTING: Six U.S. clinical sites. PARTICIPANTS: Community-dwelling men aged 65 years and older. MEASUREMENTS: Body composition measures using anthropometry (body weight, body mass index [BMI]) and dual x-ray absorptiometry (total body fat percent, trunk fat percent, ratio of trunk and total body fat). Erectile dysfunction was assessed using the single item Massachusetts Male Aging Study (MMAS) scale and the International Index of Erectile Function questionnaire (IIEF-5). RESULTS: Among men completing the MMAS scale (n=4108), prevalence of complete ED was 42%. Among sexually active men completing the IIEF-5 questionnaire (n=1659), prevalence of moderate to severe ED was 56%. In multivariate-adjusted analyses reporting prevalence ratios (PR) and 95% confidence intervals (CI), the prevalence of MMAS-defined complete ED was significantly increased in men in the highest quartile of increased body weight PR = 1.24, 95% CI = 1.16-1.34), total body fat percentage (PR = 1.25, 95% CI = 1.13-1.40), and trunk fat percentage (PR = 1.24, 95% CI = 1.15-1.38), and in men with BMI >30.0 kg/m(2) compared to those with BMI 22.0-24.9 kg/m(2) (PR = 1.17, 95% CI = 1.05-1.31). Associations appeared similar for IIEF-5 defined moderate to severe ED in analyses adjusted for age and study site. CONCLUSION: In a cohort of older men, increased body weight, BMI, and total body fat percent were independently associated with increased prevalence of moderate to severe and complete ED. Future studies should investigate whether interventions to promote weight loss and fat loss will improve erectile function in older men.